Wanting to Forget: Intrusive and Delusional Memories from Critical Illness - Lauren Doig; Kevin Solverson (Case Reports in Critical Care)
Introduction. Delusional and fearful memories after critical illness are observed in up to 70% of patients post critical illness. However, they often go unrecognized after patients leave the intensive care unit (ICU). Case Presentation. A 40-year-old male was admitted to the ICU with community-acquired pneumonia and multiorgan failure requiring mechanical ventilation and renal replacement therapy. He developed protracted delirium and severe ICU-acquired weakness but was eventually discharged home. The patient returned to a follow-up clinic two months post-ICU discharge and revealed that he was suffering anxiety from memories in the ICU of different staff trying to harm and kill him, including being repeatedly suffocated. By providing context to the memories, the patient had significant relief in his anxiety. Conclusions. Intrusive memories contribute to psychological morbidity post critical illness, including posttraumatic stress disorder (PTSD) and reduced health-related quality of life. The majority of critical illness survivors do not share their intrusive or frightening memories, and therefore, most healthcare professionals are unaware of the problems they can pose. Assessment of patients’ memories from the ICU is essential and may create the opportunity to help patients place memories into context and improve psychological morbidities.